"When the Egg Breaks, the Chicken Bleeds": unsettling coloniality through fertility in lispector's the passion according to g.h. and the chronicles. Issue 2 (4th March 2023) - van der Waal, Rodante; Schoof, Kim; van Rooden, Aukje
Abstract: Clarice Lispector has been studied thoroughly against the backdrop of Western ontology and feminism, but she has not often been read in relation to postcolonial theory and Black studies. Yet, their critique of coloniality and the radicality with which they conceive of a different world, can provide a fitting frame for understanding what is at stake in Lispector's thought. When put in dialogue with the work of Édouard Glissant and Denise Ferreira da Silva, Lispector makes a key contribution to the reconfiguration of the relation between the subject and the world that can be understood as an attempt to, echoing Sylvia Wynter, "unsettle the coloniality of being." Where Glissant effectuates "creolization" and Silva a "hacking" of the subject, Lispector attempts to transgress our colonial relation to the world through a reconfiguration of fertility. In our study of The Passion According to G.H., supported by fragments from the Chronicles, we show: (1) how the passion of G.H., is the passion of a specifically colonial subject; (2) how fertility is an essential link between subjectivity and coloniality, ensuring an atavistic chain of filiation and hence the continuation of a colonially dominated world; and (3) how Lispector reconfigures fertility as a possibility of being deeply affected by the world, so much so that the colonial subject perishes and the chain of filiation is disrupted. As a consequence, we argue that Lispector's project must not primarily be understood as ontological or in search of pre-discursivity, but as concerned with the revolutionary question of dismantling the colonial subject and its world in order to open up a potential of life otherwise .